Presenting the dynamic model of football in Qatar: The role of hosting the 2022 FIFA World Cup - Abdulateef Almohammed, Ali; Talebpour, Mahdi; Keshtidar, Mohammad; Mirzazadeh, Zahrasadat (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The current study aimed to present a dynamic football model in Qatar, concentrating on the role of hosting the 2022 FIFA World Cup. It was practical in terms of purpose and qualitative in terms of strategy. The qualitative research method was based on grounded theory, applying the Strauss-Corbin approach. The sample consisted of 22 football experts selected through purposeful sampling. These individuals represented various roles within the Qatar Stars League during the 2021-2022 football season, including coaches, referees, athletes, heads and managers of football clubs, and veterans. The main categories obtained in this research included causal conditions, contextual conditions, and intervening conditions. Finally, the dynamic model of Qatar football was presented after determining the desired model, process/interactions, consequences, and relationships between the elements. The development of new media and technology also profoundly impacted football club-media relations, as clubs recognized the importance of external communications and the demand for instant information. In general, media, technology, and investment play an important role in shaping the dynamics of the football league in Qatar, driving growth and influencing organizational strategies.